2023
DOI: 10.1002/hpja.697
|View full text |Cite
|
Sign up to set email alerts
|

What is the effect of a brief intervention to promote physical activity when delivered in a health care setting? A systematic review

Abstract: Issue AddressedWhat are the effects of a brief intervention to promote physical activity (PA) delivered in a health care setting other than primary care?MethodsMEDLINE, EMBASE, CINAHL and PsycINFO were used to identify randomised controlled trials which evaluated the effect of brief interventions to increase PA, delivered in a health care setting. Review outcomes included subjectively or objectively measured PA, adherence to prescribed interventions, adverse events, health‐related quality of life, self‐efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…6 Furthermore, a recent review of published trials on the efficacy of a brief intervention promoting physical activity demonstrated sustained change at 12 months in three studies in the cardiac healthcare setting. 16 Limitations of our study include the small sample size of junior doctors, all of whom were undertaking internships at a single hospital. Interns were working in various departments, with those on busier terms likely less able to take meal breaks and having less time at home to prepare food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Furthermore, a recent review of published trials on the efficacy of a brief intervention promoting physical activity demonstrated sustained change at 12 months in three studies in the cardiac healthcare setting. 16 Limitations of our study include the small sample size of junior doctors, all of whom were undertaking internships at a single hospital. Interns were working in various departments, with those on busier terms likely less able to take meal breaks and having less time at home to prepare food.…”
Section: Discussionmentioning
confidence: 99%
“…A health promotion strategy at Liverpool Hospital, which included provision of a water bottle and cookbook, resulted in significant improvements in employees' fruit, vegetable and water consumption at 12 weeks 6 . Furthermore, a recent review of published trials on the efficacy of a brief intervention promoting physical activity demonstrated sustained change at 12 months in three studies in the cardiac healthcare setting 16 …”
Section: Discussionmentioning
confidence: 99%
“…[11] More recent studies, focussing on brief interventions, show that brief advice on PA delivered by GPs can also enhance self-reported and measured PA levels of patients at least in the medium-term (up to six months). [12,13] Brief advice in these studies is characterised as de ned by the National Institute for Health and Care Excellence (NICE): It is offered opportunistically, includes the assessment of the PA level, brief advice on PA with negotiation or encouragement, with or without written support or follow-up. [5] A systematic review, focussing on studies with different approaches of PA advice (e.g., motivational interviewing), shows that there is no clear effect of PA advice on sedentary behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that systematically focus on brief advice approaches as de ned by the National Institute for Health and Care Excellence (NICE (19), de nition see below), show that providing brief advice on PA can effectively enhance patients' PA level in the medium term (up to six months) (20,21). However, taken together, the evidence so far does not allow clear conclusions about the long-term effects of brief advice (13).…”
Section: Introductionmentioning
confidence: 99%